2021
DOI: 10.3390/ma14206001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yttrium Addition on Structure and Magnetic Properties of Co60Fe20Y20 Thin Films

Abstract: In this paper, a Co60Fe20Y20 film was sputtered onto Si (100) substrates with thicknesses ranging from 10 to 50 nm under four conditions to investigate the structure, magnetic properties, and surface energy. Under four conditions, the crystal structure of the CoFeY films was found to be amorphous by an X-ray diffraction analyzer (XRD), suggesting that yttrium (Y) added into CoFe films and can be refined in grain size and insufficient annealing temperatures do not induce enough thermal driving force to support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Conversely, rougher surfaces exhibit higher carrier conductivity, leading to a reduction in electrical resistance. The comparison with other designated materials can be seen in Table 1, including Cobalt Iron Ytterbium (CoFeYb) and Cobalt Iron Yttrium (CoFeY), deposited on Si(100) substrates [55,56]. The information presented in Table 1 highlights that the maximum χac in the current research is lower than observed in Co60Fe20Yb20 and Co60Fe20Y20 materials.…”
Section: Characterization Of Surface Roughnessmentioning
confidence: 74%
“…Conversely, rougher surfaces exhibit higher carrier conductivity, leading to a reduction in electrical resistance. The comparison with other designated materials can be seen in Table 1, including Cobalt Iron Ytterbium (CoFeYb) and Cobalt Iron Yttrium (CoFeY), deposited on Si(100) substrates [55,56]. The information presented in Table 1 highlights that the maximum χac in the current research is lower than observed in Co60Fe20Yb20 and Co60Fe20Y20 materials.…”
Section: Characterization Of Surface Roughnessmentioning
confidence: 74%
“…Compounds are formed by combining rare-earth elements and transition metals such as iron and cobalt, and it is worthwhile to explore the performance of the resulting compounds. CoFeY alloys are frequently utilized in the magnetic-recording-head sector for write poles, yokes, and shields [18][19][20]. In more recent nanofilm literatures, the effects of thickness and annealing temperature on characteristics have been investigated [21,22].…”
Section: Introductionmentioning
confidence: 99%